Image Compression - An Overview (International Journal of Engineering and Computer Science, 2016)
vWith the continuing growth of modern communications technology, demand for digital image transmission and storage is increasing rapidly. Digital technology has given a great benefit to the area of image processing. Image compression is an economically viable alternative to these constraints by reducing the bit size required to store and represent the images, while maintaining relevant information content. The improvement of computer hardware including processing power and storage power has made it possible to utilize many-sophisticated signal processing techniques in advanced image compression algorithms.